Association of Joint Genetic and Social Environmental Risks With Incident Myocardial Infarction: Results From the Health and Retirement Study - Junhan Tang; Chen Sheng; Yan Yan Wu; Lijing L. Yan; Chenkai Wu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Myocardial infarction (MI) is a significant clinical and public health problem worldwide. However, little research has assessed the interplay between genetic susceptibility and social environment in the development of MI. Methods and Results Data were from the HRS (Health and Retirement Study). The polygenic risk score and polysocial score for MI were classified as low, intermediate, and high. Using Cox regression models, we assessed the race‐specific association of polygenic score and polysocial score with MI and examined the association between polysocial score and MI in each polygenic risk score category. We also examined the joint effect of genetic (low, intermediate, and high) and social environmental risks (low/intermediate, high) on MI. A total of 612 Black and 4795 White adults aged ≥65 years initially free of MI were included. We found a risk gradient of MI across the polygenic risk score and polysocial score among White participants; no significant risk gradient across the polygenic risk score was found among Black participants. A disadvantaged social environment was associated with a higher risk of incident MI among older White adults with intermediate and high genetic risk but not those with low genetic risk. We revealed the joint effect of genetics and social environment in the development of MI among White participants. Conclusions Living in a favorable social environment is particularly important for people with intermediate and high genetic risk for MI. It is critical to developing tailored interventions to improve social environment for disease prevention, especially among adults with a relatively high genetic risk.